The Meaning of the Lyrics of the Song Eling-Eling Umat: An Analytical Descriptive Study of the Manifestation of Submission and the Priority of Worship - Asep Firmansyah (Quality : Journal Of Education, Arabic And Islamic Studies, 2025)
This study aims to analyze the meaning of the lyrics of the song "Eling-Eling Umat" by Ebith Beat A. as a means of preaching and reminding Muslims to pray. Using descriptive analytical methods and document study, this study found that the song's lyrics are effective in raising awareness among Muslims about the importance of prayer as a primary obligation. The song's core message includes an invitation to perform congregational prayer due to its virtue, an emphasis on the quality of prayer through reverence and tranquility, and a warning against negligence and showing off. In conclusion, this song serves not only as a reminder but also as an educational medium that teaches the essential values ​​of prayer, making it not merely a ritual but also a manifestation of submission and sincerity.